An alternative to the product limit method: the multistate approach (Journal of Statistical Research, 2021)
The plan for this special volume of the Journal of Statistical Research started with Professor Dr. M. Ataharul Islam as one of the editors. Unfortunately, Professor Islam has passed away during the preparation of this volume on December 6, 2020. To honor Professor Islam’s contribution to the statistical community we have published this significant methodological work of Islam from 27 years back, originally published in the Journal of Royal Statistical Society, Series D (The Statistician). Permission to re-publish the article in JSR has been granted by the Royal Statistical Society and the JohnWiley & Sons, Inc. The original reference to the publication is here: M. Ataharul Islam: AN ALTERNATIVE TO THE PRODUCT LIMIT METHOD: THE MULTISTATE APPROACH, The Statistician 43, 237–245, 1994.Journal of Statistical Research 2021, Vol. 55, No. 1, pp. 7-20